The Dynamics of Sasi Laut Practices amidst Local Economic and Political Transformations - Satria, Arif; Mony, Ahmad (Sodality: Jurnal Sosiologi Pedesaan, 2019)
This study aims to explain the impact of socio-economic transformation, local political dynamics, and external pressures on the practice of sasi laut in Noloth Village. Data obtained using in-depth interview techniques, literature studies, and observations. The analysis and discussion is done descriptively. The results showed that there were three main things that influenced the practice of sasi laut, namely: the integration of valuable fishery products such as lola, sea cucumbers, and lobsters into the market system had changed the institution of sasi laut from the traditional system to the auction mechanism to the capital owners. While the sustainability of valuable coastal resources is threatened under transfer rights to capital owners who have unlimited resource use motives. On the other hand, sasi laut is under local political pressure between the village elite to take economic benefits. In the end, the practice of sasi laut in Noloth Village has experienced a shift in values from cultural contexts to economic reasoning through the integration of fisheries commodities into the market system. The impact of the transformation of sasi laut practices into its own discourse is related to two fundamental questions of indigenous community-based resource management, namely strengthening traditions and conservation of coastal resources.